(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ebead MAS, Hussein HNM, Gomaa H, Abdelmottaleb M, Mahdy A. 2022. The relationship between seagrass abundance, distribution and the abiotic factors in Big Gifton and Abu Minqar islands, Red Sea, Egypt. Biodiversitas 23: 2295-2303. Seagrass communities represent spatially complex and biomass-producing systems. The current research aims to understand the relationship between the abundance and distribution of seagrass communities and the abiotic factors in Big Gifton Island and Abu Minqar Island, Red Sea, Egypt. Seasonal seagrass samples were collected during 2019-2020 using line-transect and quadrat techniques. Canonical Correspondence Analysis was used to determine the effect of environmental factors on the occurrence and abundance of seagrass species. Three seagrass species, i.e., Halophila stipulacea, Halodule uninervis, and Halophila ovalis were recorded in the two islands. The most dominant seagrass species in both locations was H. stipulacea, which accounted for 54% in Big Gifton and 45% in Abu Minqar Island, while H. uninervis and H. ovalis were less numerous, with a percentage cover of 23 and 24%; and 8 and 5% in Big Gifton and Abu Minqar island, respectively. Halophila stipulacea was highest in the winter season with a percentage of 62 % and lowest in the spring (47%) in Big Gifton, whereas it was highest in the spring (62%) and lowest in the winter (47%) on Abu Minqar Island (22%). Statistical analysis showed highly significant differences between both sites and seasons in terms of conductivity, total dissolved solids, salinity, and the presence of H. uninervis and H. ovalis. On the other hand, there were non-significant differences between both sites and seasons in terms of temperatures, dissolved oxygen, oxidation-reduction potential, nitrite, nitrate, ammonia, phosphorus and the presence of H. stipulacea. Throughout the year, Big Gifton had a higher mean phosphate value than Abu Minqar Island and this may be related to the highest abundance of H. stipulacea in Big Gifton Island. The findings of this study may aid decision-makers in the management of natural resources, particularly the seagrass beds of Big Gifton and Abu Minqar Island.